Sintesis dan Optimisasi Produksi Kitosan Asal Cendawan Endofit Akar Cagar Alam ulau Dua Banten - Rida Oktorida Khastini; Aris Munandar; Indah Juwita Sari (Biota, 2019)
The cell wall component of root endophytic fungi is a main source of chitosan synthesis. This research aimed to optimize chitosan synthesis from three different isolated species of root endophytic fungi in Pulau Dua Nature Reserve, Banten Indonesia. Three species of root endophytic fungi, namely, Aspergillus niger, Aureobasidium sp., Basipetospora sp., were cultured to produce chitosan. To optimize the production of fungal chitosan, cultures were treated with different conditions such as growth medium (Oat Meal broth, Potato Dextrose Broth, CMMY Broth), pH value (4, 5, 6, 7), and temperature (25, 30, 35, 40°C). Chitosan was extracted from dried mycelium after treated on NaOH 10% at 121°C for 2 min. The degree of deacetylation (DD) of chitosan was then examined and compared with the control (shrimp chitosan). The optimum fungal chitosan condition was higher in CMMY medium, pH 5, and 30°C. The DD value of three root endophytic fungi species, Aspergillus niger, Aureobasidium sp., Basipetospora sp. were 88.5, 83.3, 80.8, respectively, which was lower than DD value resulted from control. This study indicates that Aspergillus niger was a potential endophytic fungi for chitosan synthesis.